2023
DOI: 10.1161/circgen.121.003542
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Survival Bias and Interaction Modeling in Coronary Artery Disease Risk Prediction

Abstract: Background: The 10-year Atherosclerotic Cardiovascular Disease risk score is the standard approach to predict risk of incident cardiovascular events, and recently, addition of coronary artery disease (CAD) polygenic scores has been evaluated. Although age and sex strongly predict the risk of CAD, their interaction with genetic risk prediction has not been systematically examined. This study performed an extensive evaluation of age and sex effects in genetic CAD risk prediction. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Our work builds on prior descriptions in the UK Biobank of differences in risk discrimination by sex and demonstrates that some of this difference is related to gene‐sex interactions. 1 , 4 CAD PRS distribution across sex was similar, making sex‐participation bias an unlikely driver. 5 Efforts to understand and address barriers toward improved and less biased representation of women in genomic studies are imperative to resolve PRS performance discrepancies.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Our work builds on prior descriptions in the UK Biobank of differences in risk discrimination by sex and demonstrates that some of this difference is related to gene‐sex interactions. 1 , 4 CAD PRS distribution across sex was similar, making sex‐participation bias an unlikely driver. 5 Efforts to understand and address barriers toward improved and less biased representation of women in genomic studies are imperative to resolve PRS performance discrepancies.…”
mentioning
confidence: 93%
“…Compared with men, the risk is underrecognized and diagnosis is delayed, contributing to overall worse coronary artery disease (CAD) outcomes. 1 The mechanisms for elevated risk in women remain incompletely explained by conventional risk factors. The role of varying genetic effects in this elevation remains uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 16 While it is well appreciated that PRSs perform differentially by genetic ancestry, 17 recent analyses have shown that age and sex also influence CAD PRS performance. 18 , 19 Therefore, there is a need to assess generalizability of CAD PRS, and its role in stratifying HIV‐associated CAD is not well understood. Coronary computed tomography angiography (CCTA) has emerged as a powerful tool to extract surrogate indices for clinical CAD risk to assess such novel biomarkers.…”
mentioning
confidence: 99%